KEY COMPETENCIES OF A LEADER: EVALUATION AND DEVELOPMENT TRENDS - Головньова, Ірина Володимирівна; Милославська, Олена Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The article is devoted to the identiﬁ cation of a leader key competencies and direction features of through interviews and testing. The article presents a review of theoretical studies devoted to the study of managerial competencies. Also, the directions of development of competencies, speciﬁ c for each of them, were revealed. During the interviews of managers two key competencies were deﬁ ned: «leadership», «openness to changes». Analysis of the results of the interviews and testing made it possible to specify the direction of work on the development of competency.